2018
DOI: 10.1021/acs.iecr.7b04139
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Compressed CO2 and Cotton Fibers on the Crystallization and Foaming Behaviors of Polylactide

Abstract: The foaming behavior and thermal properties of neat polylactide (PLA) and PLA/cotton-fiber composite foams were investigated in this study. CO2 saturation pressure, temperature, and fibers content significantly affected PLA’s crystallinity and foaming behaviors. At the same saturation temperature (140 °C), a low CO2 pressure generated nonuniform foam and a large unfoamed area due to too high crystallinity with a close-packed structure. At an intermediate pressure, a fine-cell structure was developed due to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 52 publications
1
18
0
Order By: Relevance
“…Kenaf/PP/PLA composites prepared at 150 °C showed a lower tensile strength with 200 MPa due to significant yield behaviour, which demonstrated a ductile fracture [32]. These are confirmed by the previous studies, which reported that the PLA materials are brittle because they consist of amorphous phases when the temperature rises between 140 °C to 180 °C [32,33]. For epoxy composites, the tensile strength decreased as the kenaf fibres loading increased, predominantly because of the poor matrix adhesion and unbonding between the matrix and fibres [34].…”
Section: Resultssupporting
confidence: 69%
“…Kenaf/PP/PLA composites prepared at 150 °C showed a lower tensile strength with 200 MPa due to significant yield behaviour, which demonstrated a ductile fracture [32]. These are confirmed by the previous studies, which reported that the PLA materials are brittle because they consist of amorphous phases when the temperature rises between 140 °C to 180 °C [32,33]. For epoxy composites, the tensile strength decreased as the kenaf fibres loading increased, predominantly because of the poor matrix adhesion and unbonding between the matrix and fibres [34].…”
Section: Resultssupporting
confidence: 69%
“…Gas foaming is attracting more and more interest from researchers because of its advantages of being free of organic solvents and eco-friendly. 13,14 During this process, carbon dioxide (CO 2 ), which is as widely used as it is inexpensive, non-toxic, highly dissolvable in polymers, recoverable, and reusable, is rst dissolved into a polymer melt at a certain temperature and pressure. Aer the CO 2 turns to a supercritical uid (SCF), it is depressurised to ambient levels to trigger the nucleation.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, as these grades are commercialized, they are most probably additivated with nucleating agents by the manufacturer. Also other studies have only revealed a moderate density reduction for batch foamed PLA injection molding grades [35,36]. during the stretching, while the expansion (so called strain induced crystallization) [20].…”
Section: Expansion Of the Neat Gradesmentioning
confidence: 98%